Analysis and prevention of microbial degradation of shadow puppetry artifacts preserved in the National Shadow Puppetry Museum in Chengdu - Wang, Yu; Wang, Yuanyuan; Guan, Zhiqian; Wang, Zeao; Duan, Yangbo; Min, Chen; Zhong, Yuhan; Hou, Lilong; Pan, Jiao (Frontiers in Microbiology, 2025)
Shadow puppetry, an integral and crucial component of China’s intangible cultural heritage, currently faces the significant threat of microbial degradation. This is primarily due to the organic materials used in its artifacts. This study centers on the shadow puppets housed in the National Shadow Puppetry Museum in Chengdu. By employing Scanning Electron Microscopy (SEM) and high-throughput sequencing techniques, it has revealed a diverse array of co-existing microorganisms on the surfaces of these puppets. These include species from genera such as Aspergillus, Streptomyces, Nocardiopsis, Pseudomonas, and Saccharopolyspora, among others. Eleven microbial species were successfully isolated, wherein four were identified as predominant: Pseudomonas sp. WH. S-B1, Streptomyces sp. WH. S-B2, Nocardiopsis sp. WH. S-B6, and Aspergillus fumigatus WH. S-F2. Notably, these four strains demonstrated the ability to degrade collagen. The antimicrobial experiment results indicated that 0.3% isothiazolinone-based antimicrobial agents BC01 and 50 mg/mL carvacrol exhibited a certain degree of antimicrobial activity against these predominant strains. Overall, this research provides a robust foundation for the conservation of shadow puppet artifacts. It does so by thoroughly analyzing the mechanisms of microbial degradation and screening effective antimicrobial agents.